2017
DOI: 10.3390/ijms18102173
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-Inducers Counteract Neurodegeneration in Frataxin-Silenced Motor Neurons: Disclosing New Therapeutic Targets for Friedreich’s Ataxia

Abstract: Oxidative stress is actively involved in Friedreich’s Ataxia (FA), thus pharmacological targeting of the antioxidant machinery may have therapeutic value. Here, we analyzed the relevance of the antioxidant phase II response mediated by the transcription factor Nrf2 on frataxin-deficient cultured motor neurons and on fibroblasts of patients. The in vitro treatment of the potent Nrf2 activator sulforaphane increased Nrf2 protein levels and led to the upregulation of phase II antioxidant enzymes. The neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 54 publications
5
63
1
Order By: Relevance
“…Considering that in CX3CR1-deficient mice there is a reduction of the NRF2 axis in microglial cells, we evaluated the effect of an inducer of NRF2 as a possible modulator of this effect with putative implications the neuroinflammatory associated to tauopathies. Moreover, it has been reported that NRF2 induction has neuroprotective effects in several neurodegenerative mouse models (Jazwa et al, 2011, Lastres-Becker et al, 2016, Petrillo, Piermarini et al, 2017, Phillips & Fox, 2013 as well as in tauopathies . Thus, the effects of SFN on neuroinflammation were examined in Cx3cr1 +/+ and Cx3cr1 -/mice stereotaxically injected in the right hippocampus with AAV-TAU P301L and treated daily with SFN (50mg/kg, i.p) during three weeks.…”
Section: Sfn Treatment Reverses Astrogliosis But Not Microgliosis In mentioning
confidence: 99%
“…Considering that in CX3CR1-deficient mice there is a reduction of the NRF2 axis in microglial cells, we evaluated the effect of an inducer of NRF2 as a possible modulator of this effect with putative implications the neuroinflammatory associated to tauopathies. Moreover, it has been reported that NRF2 induction has neuroprotective effects in several neurodegenerative mouse models (Jazwa et al, 2011, Lastres-Becker et al, 2016, Petrillo, Piermarini et al, 2017, Phillips & Fox, 2013 as well as in tauopathies . Thus, the effects of SFN on neuroinflammation were examined in Cx3cr1 +/+ and Cx3cr1 -/mice stereotaxically injected in the right hippocampus with AAV-TAU P301L and treated daily with SFN (50mg/kg, i.p) during three weeks.…”
Section: Sfn Treatment Reverses Astrogliosis But Not Microgliosis In mentioning
confidence: 99%
“…It is interesting remembering that NRF2, in turn, activates the transcription of antioxidant and detoxifying genes such as catalase, superoxide dismutases or thioredoxin reductase [72]. In this context, the beneficial effects of calcitriol, as a natural NRF2 inducer, are in agreement with one of the emerging therapies for FA is based on the activation of NRF2 including sulphoraphane [73], dimethyl fumarate [74] or omaveloxolone [75,76].…”
Section: The Beneficial Role Of Calcitriol In Neurodegenerative Diseamentioning
confidence: 87%
“…The Nrf2 pathway is activated by several cytotoxic factors and produces multiple cellular responses by inducing the expression of genes involved in glutathione metabolism (GCL and GR) in the detoxification of xenobiotics (NQO1) in inflammation and in the neutralization of reactive oxygen species. 18,19,22 PD preclinical models have demonstrated that the Nrf2 pathway has reciprocal interactions with 2 key determinants of disease pathogenesis, namely, synucleinopathy and mitochondrial impairment, 12,13,[23][24][25][26] such that it could represent either an index of cellular impairment or a disease-modifying treatments' target. We translated this preclinical evidence on clinical grounds, exploring the Nrf2 pathway in vivo in PD through an analysis of its downstream effectors and relevant upstream factors in the blood leukocytes of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 32 PD and 32 CTL samples, blood Reduced Glutathione/Oxidized Glutathione (GSH/GSSG) levels, mitochondrial complex I (CI) and citrate synthase (CS) enzyme activity were assessed by enzymatic recycling, MitoSciences dipstick (Abcam, Cambridge, UK), and spectrophotometric assays, respectively. Biochemical analyses were performed blindly at Bambino Gesù Hospital (Rome, Italy), which has long‐term expertise in this field …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation